Kontribusi Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPS di SMP Negeri 2 Secanggang Desa Karang Anyar - Syakrawi, Mutawalli; Ponidi, Ponidi (PAKAR Pendidikan, 2025)
Students learn, change attitudes, and develop life skills inside and outside school by following and obeying the rules in structured education. This study was conducted to analyze and find out what factors affect student motivation to learn social studies and to know the role and contribution of the school environment to student learning motivation. This study uses a descriptive qualitative method, the sampling technique of which is purposive sampling, to determine the research sample. For data collection techniques used are library research and field research, including observation, interviews, and documentation. The results showed that the school environment influences student learning motivation to facilitate the teaching and learning process. Physical factors, such as classroom facilities and cleanliness, affect children's sense of comfort and safety in the school environment. Social interactions between learners, teachers, and education personnel are part of the school environment, which is very important in fostering harmony, collaboration, and a sense of unity in the school community, ultimately impacting students' academic drive. Teacher factors include teaching methods and exemplary school atmosphere and conditions, school friends (classmates), student health, talents possessed by each student, facilities, and infrastructure, completeness of learning tools and media, and family support, which all affect student learning motivation. The presence of complete facilities improves the quality of social studies learning, qualified teachers, a comfortable and clean school environment, and encouragement and motivation from social studies teachers.